PREVALENCE OF THE Anguillicola crassus PARASITE IN THE INTERNATIONAL MINHO RIVER - Luís Pereira; Ana Catarina Braga; Ana Moura; Carlos Antunes (ENVIRONMENTAL SMOKE, 2022)
The European eel, Anguilla anguilla (Linnaeus, 1758), is vulnerable to infections by the parasitic nematode Anguillicola crassus Kuwahara, Niimi & Itagaki, 1974, mainly in freshwater ecosystems. The eel is a bioindicator species due to its benthic behaviour, predator, and life cycle. The parasite feeds on blood from the eel's swim bladder, causing damage to the walls and deterioration of this organ, reducing energy reserves, and affecting its migratory capacity for reproduction. Eels were captured at different sampling points divided into 4 areas of the international section of the Minho River in the following time periods: 1995-96, 2008-2011 and 2017-2021, through fyke nets and electric fishing sampling techniques. The objectives of this work were to analyze the dispersion and prevalence of A. crassus in the Minho River basin over time, infection rates and the eels condition. The prevalence levels found reach values close to 75% in some sampled locations and 99% of eels shown pathological signs of swim bladder infection. The nematode dispersal area increased since the early 1990s when its presence in the Minho River was first recorded.